Pengaruh mutu pelayanan kesehatan terhadap kepuasan pasien peserta JKN/KIS di Puskesmas Gunung Tua Kecamatan Padang Bolak - Sri Dewi; Thomson P Nadapdap; Neni Ekowati Januariana (Jurnal Kesmas Prima Indonesia, 2022)
Quality of health services is the level of perfection of health services, which on the one hand can lead to satisfaction for each patient in accordance with the average level of satisfaction. The purpose of this study was to analyze the quality of service that affects patient satisfaction of JKN / KIS participants at Gunung Tua Publich Health, Padang Bolak District, North Padang Lawas Regency in 2020. This study used a quantitative analytical survey with a cross sectional study design. The location of this research was conducted at Gunung Tua Puskesmas, Padang Bolak District, North Padang Lawas Regency. The study population was all outpatients visiting with an average monthly visit of 906 patients. The number of samples in this study were 90 people. The technique used is purposive sampling. Survey data were analyzed using the chi-square test and logistic regression. The results showed that there was an effect of tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (certainty) and empathy (empathy) had an effect on patient satisfaction of JKN / KIS participants at Gunung Tua Puskesmas, Padang Bolak District, North Padang Lawas Regency. Based on the research results, it is known that the variable that most influences patient satisfaction is the responsiveness variable (responsiveness). It is recommended for health workers to maintain patient satisfaction by improving the quality of service, especially in the responsiveness aspect, such as responding to complaints quickly, so that patients feel valued and served well and increasing the number of officers who handle JKN / KIS patients so that patients do not wait too long